Resposta :
Resposta:
f(x) = (x-1)^2 +4
Sem interceção -x / zero
Explicação passo a passo:
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo a passo:
[tex]\mathsf{f(x) = x^2 - 2x + 5}[/tex]
[tex]\mathsf{\Delta = b^2 - 4.a.c}[/tex]
[tex]\mathsf{\Delta = (-2)^2 - 4.1.5}[/tex]
[tex]\mathsf{\Delta = 4 - 20}[/tex]
[tex]\mathsf{\Delta = -16}[/tex]
[tex]\mathsf{a)\:N{\~a}o\:intersecta\:\Delta < 0 }[/tex]
[tex]\mathsf{b)\:A(0,c) = A(0,5) }[/tex]
![Ver imagem AUDITSYS](https://pt-static.z-dn.net/files/d1a/68f1a8105948ca3b3e61602dbc1d0525.jpg)